2022
DOI: 10.1038/s41598-022-22704-0
|View full text |Cite
|
Sign up to set email alerts
|

Travel time optimization on multi-AGV routing by reverse annealing

Abstract: Quantum annealing has been actively researched since D-Wave Systems produced the first commercial machine in 2011. Controlling a large fleet of automated guided vehicles is one of the real-world applications utilizing quantum annealing. In this study, we propose a formulation to control the traveling routes to minimize the travel time. We validate our formulation through simulation in a virtual plant and authenticate the effectiveness for faster distribution compared to a greedy algorithm that does not conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This allows us to search for a better solution. Haba's study 11 has shown that reverse annealing makes it easier to obtain the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…This allows us to search for a better solution. Haba's study 11 has shown that reverse annealing makes it easier to obtain the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…RA is utilized to seek a more optimal solution. There have been instances where RA has expedited the search for solutions with high accuracy using shorter annealing schedules than those in QA (FA) [34,35]. This paper extends this approach and presents a method that employs reverse annealing to enhance the efficiency of MOT.…”
Section: Enhanced Mot Through Ramentioning
confidence: 99%
“…With the constant improvement of information technology and the establishment of autonomous factories, automatic guided vehicles (AGVs) are gradually being used in the workshop to transport workpieces [1][2][3][4][5]. The performance of a workshop is affected in many aspects [6].…”
Section: Introductionmentioning
confidence: 99%